INFLUENCE OF THE PROBABILTY LEVEL ON THE FRAMING EFFECT IN REFERENCE POINT OF LOSS - Gvozdenović, Vasilije; Damnjanović, Kaja (Primenjena psihologija, 2016)
Framing effect, which refers to preference reversal due to different descriptions of the same outcome, is examined through risky choice tasks, in which experimental reference point is typically positioned in win-area (situation of lottery). The aim of the conducted study was to examine a framing effect pattern as a function of the level of risk in risky options when experimental reference point is positioned in loss-area (paying a bill). Results show general loss aversion in monetary domain, which is in an accordance with previous studies. Frame influences decisions in the situations when possibility of total loss (level of risk) is perceived as relatively low. Interpretation of these results leads to the conclusion that the probability and reference point determine framing effect. In win-area, frame influences decisions on the highest levels of probability, and, vice-versa, in loss-area, frame influences decisions on the lowest levels of probability. Results confirm notion that risk-aversion is dependent upon a decision-maker’s perception of spending (an investment or a loss). Although observed risk-seeking decisions in negative frame and different decision patterns in loss and win areas can be explained by the model of cumulative prospect-theory, influence of different experimental reference point can not.